2007
DOI: 10.1539/joh.49.134
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle‐Determined Gender and Hierarchical Differences in the Lead Contamination of Bones from a Feudal Town of the Edo Period

Abstract: Lifestyle-Determined Gender and Hierarchical Differences in the Lead Contamination of Bones from a Feudal Town of the Edo Period: Tamiji NAKASHIMA, et al. Department of Anatomy, University of Occupational and Environmental Health, Japan-We analyzed lead concentrations in bones from both genders of Japanese merchants (including rohnin; masterless samurai) and farmer classes, and compared the findings with those of the samurai class in the Edo period (1603-1867) to clarify gender and hierarchical (or occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Exposures to Pb are highest in the Edo era in Japan as reported by others [22][23][24][25]. No trend was observed in this study in the Hg content of teeth for 3,000 years in Japan.…”
Section: Long-term Trend and Data Interpretationcontrasting
confidence: 42%
See 1 more Smart Citation
“…Exposures to Pb are highest in the Edo era in Japan as reported by others [22][23][24][25]. No trend was observed in this study in the Hg content of teeth for 3,000 years in Japan.…”
Section: Long-term Trend and Data Interpretationcontrasting
confidence: 42%
“…However, Pb levels are widely scattered among samples, likely reflecting personal lifestyles or habits. As a matter of fact, it is reported that lead-oxide cosmetic powders were used by females of the Samurai classes or merchants in urban centers in the Edo era [22][23][24][25]. Thus, higher exposures to Pb found in teeth samples of two subjects in the merchant class in the Edo era can likely be explained by the use of the lead-containing cosmetics by the mother.…”
Section: Long-term Trend and Data Interpretationmentioning
confidence: 99%
“…Studies have reported contamination of IFM by various substances such as nitrates, nitrites, aluminium (Al), cadmium (Cd), mercury (Hg), nickel (Ni), lead (Pb) and melamine (Gian et al, 2009;Khalifa and Ahmad, 2010;Burrell andExley, 2010 andLjung et al, 2011). In 2008, melamine contamination of IFM in China led to deaths and illness of several infants (Nakashima et al, 2009). China reported an estimated 300,000 victims with approximately 54,000 babies being hospitalized and six infants dying from kidney stones and other kidney damage (Branigan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that human Pb contamination in Japan began in preindustrialized Edo era (1603-1867) probably through the usage of cosmetics (Hisanaga et al 1988;Nakashima et al 1998Nakashima et al , 2007. After Edo era, industrialization started and Pb emission from industrial activities to the environment should have affected human body burden of Pb.…”
Section: Introductionmentioning
confidence: 99%